Answer:
[tex]1,207.6\ m[/tex]
Step-by-step explanation:
step 1
Find the perimeter of one lap
we know that
The perimeter of one lap is equal to the circumference of a complete circle (two half circles is equal to one circle) plus two times the length of 96 meters
so
[tex]P=\pi D+2(96)[/tex]
we have
[tex]D=35\ m[/tex]
[tex]\pi =3.14[/tex]
substitute
[tex]P=(3.14)(35)+2(96)[/tex]
[tex]P=301.9\ m[/tex]
step 2
Find the total meters of four laps
Multiply the perimeter of one lap by four
[tex]P=301.9(4)=1,207.6\ m[/tex]
Answer:
1207.6
Step-by-step explanation:
step 1
i got it right on the test
step 2
you get it right on the test
You brought 9 feet of elastic to make hair ties each hair ties need 3 3/8 inches of elastic how many hair ties can you make
Answer:
[tex]32\ hair\ ties[/tex]
Step-by-step explanation:
we know that
To make one hair ties is needed 3 3/8 inches of elastic
so
using proportion
Find out how many hair ties can you make with 9 feet of elastic
Remember that
[tex]1\ ft=12\ in[/tex]
Convert 9 ft to inches
[tex]9\ ft=9*12=108\ in[/tex]
Convert mixed number to an improper fraction
[tex]3\frac{3}{8}\ in=\frac{3*8+3}{8}=\frac{27}{8}\ in[/tex]
using proportion
[tex]\frac{1}{(27/8)}=\frac{x}{108}\\\\x=108*8/27\\\\x=32\ hair\ ties[/tex]
#23-6: The pool concession stand made $5,800 in June and $6,300 in July. What is the percent of increase in sales? Round the answer to the nearest tenth.
Answer:
8.6%
Step-by-step explanation:
To find the percent change, you will need to compute the positive difference and then divide the difference by the original (the older amount).
So the positive difference will be obtain by doing larger minus smaller:
6300
- 5800
-----------
500
The older amount was 5800.
So 500/5800 is the answer as a un-reduced fraction.
I'm going to reduce it by dividing top and bottom by 100:
500/5800 = 5/58
5/58 is the answer as a reduced fraction.
5 divided by 58 gives=0.086206897 in the calculator .
Approximately 0.0862 is the answer as a decimal.
To convert this to a percentage, multiply it by a 100:
8.62%
Rounded to the nearest tenths is 8.6%
-------------
So 5800+5800(.0862) should be pretty close to 6300 (not exactly though since we rounded).
5800+5800(.0862)=6299.96 using the calculator.
Find the midpoint of the segment between the points (15,−9) and (−2,−18)
Answer:
(13/2, -27/2)
Step-by-step explanation:
The midpoint is found by using
midpoint = (x1+x2)/2, (y1+y2)/2
= (15+-2)/2, (-9+-18)/2
=13/2, -27/2
What is the value of y?
Y + 30°
A. 85°
B. 55
c. 110°
D. 10°
Answer:
B. 55°
Step-by-step explanation:
Note that the total angle measurements of a triangle is = 180°.
Add all the measurements together:
40 + y + 30 + y = 180
Simplify. Combine like terms:
(40 + 30) + (y + y) = 180
70 + 2y = 180
Isolate the y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. First subtract, then divide.
Subtract 70 from both sides:
70 (-70) + 2y = 180 (-70)
2y = 180 - 70
2y = 110
Divide 2 from both sides:
(2y)/2 = (110)/2
y = 110/2
y = 55
B. 55° is your answer.
~
Answer: The answer is B, 55 degrees.
Step-by-step explanation:
You substitute 55 into y, making it 55+85, +55, +40, making it 180 degrees. Since all sides in a triangle add up to 180, B is your correct answer.
Hope that helps!
What is the x-intercept of the line shown below? Enter your
answer as a coordinate pair.
Answer:
(0,3)
Step-by-step explanation:
The x-intercept is the point in the graph where x=0. On the graph you can see that when x=0, y=3. Therefore our coordinate is (0,3)
Our coordinate pair in the graph is (0,3)
The x-intercept of a line occurs where the line intersects the x-axis, meaning the y-coordinate is zero. In the provided graph, when x equals zero, the corresponding y-value is three. Thus, the coordinate pair (0,3) represents the point where the line intersects the x-axis. This result indicates that when x equals zero, the line crosses the y-axis at a height of three units.
To find the x-intercept, one sets y equal to zero and solves for x. In this case, when y equals zero, there is no such point on the line, so the x-intercept does not exist. Therefore, the coordinate (0,3) accurately identifies the x-intercept of the given line, demonstrating the point where it intersects the x-axis on the graph.
What is the value of -4 squared +(5-2)(-6)
-------
I need help ASAP!!!
-4^2= 16
anytime you have a negative number squared it results in the positive version
ex. -4×-4 equals -16, except it should be positive instead of negative.
now 16+-10×-6
-10×-6=60
16+60=76
Please vote my answer brainliest. thanks!
Which is the end point of a ray
Answer:
Point S is the endpoint of a ray.
Step-by-step explanation:
A ray is a line with a single endpoint (or point of origin) that extends infinitely in one direction. Point S is the endpoint for rays SR, SU, and ST.
The ray's endpoint is Point S.
Given is a figure of an angle S being divided into two angles by the ray SU,
We need to find the endpoint of the ray,
So,
A ray's endpoint is the singular location where the ray comes to an end.
A ray is a line that emanates from an initial point known as the endpoint or origin and travels endlessly in one direction.
A ray, as opposed to a line segment, has no set length and travels in one direction indefinitely.
A ray's terminus, which is also its beginning point, is typically identified as a single point in space.
A ray is a line that has a single terminus (or point of origin) and travels in a single direction indefinitely.
The intersection of rays SR, SU, and ST is at point S.
Hence the ray's endpoint is Point S.
Learn more about ray of a line click;
https://brainly.com/question/13144568
#SPJ6
What is sqrt12x^8/sqrt3x^2 in simplest form
[tex]\bf \cfrac{\sqrt{12x^8}}{\sqrt{3x^2}}~~ \begin{cases} 12=&2\cdot 2\cdot 3\\ &2^2\cdot 3\\ x^8=&x^{4\cdot 2}\\ &(x^4)^2 \end{cases}\implies \cfrac{\sqrt{2^2\cdot 3(x^4)^2}}{\sqrt{3x^2}}\implies \cfrac{2\stackrel{x^2}{~~\begin{matrix} x^4 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~} ~~\begin{matrix} \sqrt{3} \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix} x^2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~ ~~\begin{matrix} \sqrt{3} \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies 2x^2[/tex]
Answer:
2x^3 (C on edge)
Step-by-step explanation:
Solve by completing the square. x2+6x−6=0
For this case we must solve the following equation by completing squares:
[tex]x ^ 2 + 6x-6 = 0[/tex]
We add 6 to both sides of the equation:
[tex]x ^ 2 + 6x = 6[/tex]
We divide the middle term by 2, and square it:
[tex](\frac {6} {2}) ^ 2[/tex]
And we add it to both sides of the equation:
[tex]x ^ 2 + 6x + (\frac {6} {2}) ^ 2 = 6 + (\frac {6} {2}) ^ 2\\x ^ 2 + 6x + (3) ^ 2 = 6 + 9[/tex]
We rewrite the left part of the equation:
[tex](x + 3) ^ 2 = 15[/tex]
We apply root to both sides:
[tex]x + 3 = \pm \sqrt {15}[/tex]
We have two solutions:
[tex]x_ {1} = \sqrt {15} -3\\x_ {2} = - \sqrt {15} -3[/tex]
Answer:
[tex]x_ {1} = \sqrt {15} -3\\x_ {2} = - \sqrt {15} -3[/tex]
Answer:
[tex]x=-3\±\sqrt{15}[/tex]
Step-by-step explanation:
We have the following equation
[tex]x^2+6x-6=0[/tex]
To use the method of completing squares you must take the coefficient of x and divide it by 2 and square the result.
[tex](\frac{6}{2})^2=9[/tex]
Now add 9 on both sides of equality
[tex](x^2+6x+ 9)-6=9[/tex]
Factor the term in parentheses
[tex](x+3)^2-6=9[/tex]
Add 6 on both sides of the equation
[tex](x+3)^2-6+6=9+6[/tex]
[tex](x+3)^2=15[/tex]
Take square root on both sides of the equation
[tex]\sqrt{(x+3)^2}=\±\sqrt{15}[/tex]
[tex]x+3=\±\sqrt{15}[/tex]
Subtract 3 from both sides of the equation.
[tex]x+3-3=-3\±\sqrt{15}[/tex]
[tex]x=-3\±\sqrt{15}[/tex]
In ABC, O is the centroid of the triangle and AO is 12.7 m. Find the length of OY and AY.
Answer:
[tex]\boxed{OY = 6.35 m} \\\boxed{AY=19.05 m}[/tex]
Step-by-step explanation:
The centroid of a triangle always cuts a triangle perfectly at 2/3.
What I mean by this is that the line that touches the tip of the triangle and touches the median of the base is cut into one third and its other part is cut into two thirds of the whole segment. This segment is AY.
Knowing this, I can tell that OY is 1/3 of the length of AO, which is given to be 12.7 m.
To find OY, make an equation where AO and OY add up to AY.
[tex]12.7+\frac{1}{3} x=x[/tex]The variable x represents the length of AY, and 1/3x represents the length of OY (because it is one-third of AY).
Solve the equation by subtracting 1/3x from both sides.
[tex]12.7=\frac{2}{3} x[/tex]Divide both sides by 2/3.
[tex]x=19.05[/tex]Now we know the length of AY (x). To find the length of OY substitute this value of x into 1/3x, which represents OY.
[tex]\frac{1}{3} (19.05)[/tex]
This gives us 6.35, which is the length of OY.
The final answers are:
OY = 6.35 mAY = 19.05 mhow do you find the vertex of this equation: y = 6x-x2
Answer:
(3,9)
Step-by-step explanation:
This is a quadratic equation.
A quadratic in standard form is [tex]y=ax^2+bx+c[/tex].
If we compare [tex]y=ax^2+bx+c[/tex] to [tex]y=6x-x^2[/tex], we see there [tex]c=0,b=6,a=-1[/tex].
Now to find the vertex, we first find the x-coordinate of the vertex which is:
[tex]\frac{-b}{2a}[/tex].
So now plug in our values:
[tex]\frac{-6}{2(-1)}=\frac{-6}{-2}=3[/tex]
So the corresponding y-coordinate can be found by the equation that relates x to y: [tex]y=6x-x^2[/tex].
So we are plugging in 3 where we see x: [tex]y=6(3)-3^2=18-9=9[/tex].
So the vertex is (3,9).
What is the solution to the equation
1/4x+2=-5/8x-5
Answer: x = -8
Step-by-step explanation:
First you change 1/4 to 2/8. Then you want to get all of your x values on one side. So, +5/8x to each side turning your equation into 7/8x+2= -5. Then -2 from each side. 7/8x= -7. Finally get your variable by itself. Divide each side by 7/8 or multiple each side by its reciprocal (8/7)
Ellie wants to change her password which is ELLIE9 but with same letters and number. In how
many ways she can do that?
P = 256
P = 150
P = 200
P = 179
[tex]\dfrac{6!}{2!2!}-1=\dfrac{3\cdot4\cdot5\cdot6}{2}-1=180-1=179[/tex]
The number of passwords she can create is an illustration of permutations.
The number of ways to create the password is 179
The password is given as: ELLIE9
The number of characters in the password is:
[tex]n = 6[/tex]
L and E are repeated twice.
So, we have
[tex]L = 2[/tex]
[tex]E = 2[/tex]
The number of new passwords to create is then calculated as:
[tex]Passwords = \frac{n!}{L!E!} - 1[/tex] --- 1 represents the current password
This gives
[tex]Passwords = \frac{6!}{2!2!} - 1[/tex]
Expand
[tex]Passwords = \frac{6 \times 5 \times 4 \times 3 \times 2!}{2! \times 2 \times 1} - 1[/tex]
[tex]Passwords = \frac{6 \times 5 \times 4 \times 3 }{2 \times 1} - 1[/tex]
Simplify
[tex]Passwords = 180 - 1[/tex]
Subtract
[tex]Passwords = 179[/tex]
Hence, the number of ways to create the password is 179
Read more about permutations at:
https://brainly.com/question/1216161
1200 people visited a museum. 240 of the visitors were children. what percent of the visitors were children?
Answer:
20 percent
Step-by-step explanation:
To find the percentage that were children, we take the number of children over the total and multiply by 100%
There are 240 children and 1200 total people
240/1200 * 100%
.2*100%
20%
Answer:
20 Percent.
Step-by-step explanation:
240:1200*100 =
(240*100):1200 =
24000:1200 = 20
A distance of 150 km was covered by a motorcyclist traveling at an average speed of 75 km/h, by a bus at 60 km/h, a truck at 50 km/h, and a bicyclist at 20 km/h. How much time did each require to travel the entire distance? Explain why speed and the time needed to travel 150 km are inversely proportional quantities?
I need to know how to explain the last sentence.
Answer:
Motorcyclist: 2 hours
Bus: 2.5 hours
Truck: 3 hours
Bicyclist: 7.5 hours
Step-by-step explanation:
The equation of line CD is y = -2x - 2. What is the equation of a line parallel to line CD in slope-intercept form that contains point (4,5)?
Answer:
y=-2x+13
Step-by-step explanation:
Slope-intercept form of a line is y=mx+b where m is slope and b is y-intercept.
The slope of y=-2x-2 is -2 since m=-2.
A line that is parallel to the given line is going to have the same slope.
So we already know the equation we are looking for should be in the form y=-2x+b.
We just to need to find b.
We can use the given point on our line do that.
5=-2(4)+b
5=-8+b
8+5=b
13=b
So the equation is y=-2x+13.
Answer:
y = -2x+13
Step-by-step explanation:
The slope of the original line is -2 so you take that and plug it in with the points (4,5) in point slope form to get y-5 = -2(x-4), then you simplify to get y-5 = -2x+8 then y = -2x+13
If N || P and P bisects M then _____ (13)
If N || P and P bisects M then, line N must be perpendicular to line M (N ⊥ M) (option A).
How to determine the relationship between line N and line P?
From the given diagram we are told that line N is parallel to line P and line P is perpendicular to line M.
So line P bisect line M and it is also perpendicular to line M, we can deduce the following;
line N is perpendicular to line M
So based on the information given to us, we can only deduce the relationship between M, N and P.
Hence N must be parallel to P, then line P must be perpendicualr to line M and line N and line M must be perpendicular to each other.
Write the equation of the line that passes through the points (0, -6) and (-4, 0).
Show how you arrived at your answer.
What would be the EQUATION? I’m confused. Please help.
Answer:
The slope is -3/2.
Step-by-step explanation:
Hint: slope formula:
[tex]\displaystyle \frac{y_2-y_1}{x_2-x_1}=\frac{rise}{run}[/tex]
[tex]\displaystyle \frac{0-(-6)}{(-4)-0}=\frac{6}{-4}=\frac{6\div2}{-4\div2}=\frac{3}{-2}=-\frac{3}{2}[/tex]
[tex]\Large \textnormal{Therefore, the slope is -3/2.}[/tex]
Answer:
y=(-3/2)x+-6
or
y=(-3/2)x-6
Step-by-step explanation:
We are going to use slope-intercept form to find the equation for this line.
y=mx+b is slope-intercept form where m is the slope and b is the y-intercept.
y-intercept means where it crosses the y-axis; the x will be 0 here. Look the question gives us the y-intercept which is -6.
So we already know b which is -6.
y=mx+-6
Instead of finding the slope using the slope formula which you could.
I'm going to plug in the point (-4,0) into y=mx+-6 to find m.
So replace x with -4 and y with 0 giving you:
0=m(-4)+-6
0=-4m-6
Add 6 on both sides:
6=-4m
Divide both sides by -4:
6/-4=m
Reduce the fraction:
-3/2=m
The slope is -3/2.
Again you could use the slope formula which says [tex]m=\frac{y_2-y_1}{x_2-x_1} \text{ where } (x_1,y_1) \text{ and } (x_2,y_2) \text{ are points on the line}[/tex].
This is the same thing as lining the points up vertically and subtracting the points vertically then putting 2nd difference over first difference. Like this:
( 0 , -6)
-( -4 , 0)
---------------
4 -6
The slope is -6/4 which is what we got doing it the other way.
So the equation with m=-3/2 and b=-6 in y=mx+b form is
y=(-3/2)x+-6
or
y=(-3/2)x-6
Nick is solving the equation 3x2=20−7x with the quadratic formula.
Which values could he use for a, b, and c?
a = 3, b = −7 , c = 20
a = 3, b = 7, c = −20
a = 3, b = −20 , c = 7
a = 3, b = 20, c = −7
Answer: Second option.
Step-by-step explanation:
Given a Quadratic equation in the form:
[tex]ax^2+bx+c=0[/tex]
It can be solve with the Quadratic formula. This is:
[tex]x=\frac{-b\±\sqrt{b^2-4ac} }{2a}[/tex]
In this case, given the Quadratic equation:
[tex]3x^2=20-7x[/tex]
You can rewrite it in the form [tex]ax^2+bx+c=0[/tex]:
- Subtract 20 from both sides of the equation:
[tex]3x^2-20=20-7x-20\\\\3x^2-20=-7x[/tex]
- Add [tex]7x[/tex] to both sides of the equation:
[tex]3x^2-20+7x=-7x+7x\\\\3x^2+7x-20=0[/tex]
Therefore, you can identify that:
[tex]a=3\\b=7\\c=-20[/tex]
Answer:
option B. a=3, b=7, c=-20
I just took the test :)
Step-by-step explanation:
a brokerage firm charges 1 1/4% if its fee on stock purchase was 400$ what was amount of purchase?
let's say the amount purchased was "x", so then that's the 100%.
if we know that 400 is the 1¼% and "x" is the 100%, what is "x"?
[tex]\bf \begin{array}{ccll} amount&\%\\ \cline{1-2} x&100\\ 400&1\frac{1}{4} \end{array}\implies \cfrac{x}{400}=\cfrac{100}{1\frac{1}{4}}\implies \cfrac{x}{400}=\cfrac{100}{\frac{1\cdot 4+1}{4}}\implies \cfrac{x}{400}=\cfrac{\frac{100}{1}}{\frac{5}{4}} \\\\\\ \cfrac{x}{400}=\cfrac{\stackrel{20}{~~\begin{matrix} 100 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}}{1}\cdot \cfrac{4}{~~\begin{matrix} 5 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies \cfrac{x}{400}=80\implies x=32000[/tex]
Last week, a coral reef grew 20.3 mm taller. How much did it grow in meters?
Answer:
0.0203 meters
Step-by-step explanation:
If a coral reef grew 20.3 mm taller, it grew 0.0203 meters taller.
20.3 mm = 0.0203 meters
The coral reef grew by 20.3 millimeters last week, which is equivalent to 0.0203 meters. This is calculated by dividing the millimeters by 1000, as there are 1000 millimeters in a meter.
Explanation:The amount of growth in the coral reef's height can be converted from millimeters to meters by using the conversion ratio of 1 meter being equal to 1000 millimeters. So, to find out how much the coral reef grew in meters, we would take the growth in millimeters (20.3 mm) and divide by 1000.
The calculation would be like this: 20.3 mm / 1000 = 0.0203 meters.
So, the coral reef grew by 0.0203 meters last week.
Learn more about Unit Conversion here:https://brainly.com/question/32030244
#SPJ2
Which choice is equivalent to the expression below?
Square root of -17
A.-3sqr of 3i
B.-sqr of 27
C.-3sqr of 3
D.3sqr of 3
E.3i sqr of 3
Answer:
d
Step-by-step explanation:
3×3×3 is 27 so that's the answer
Explain the effect of c on the graph of y=f(x) for the function y=f(x)+c ?
Answer:
Shifts it up c units.
Step-by-step explanation:
The '+ c' will move the whole graph upwards c units.
By translation of axis, the effect of c on the graph of y=f(x) for the function y=f(x)+c is it shifts up the curve by c units.
What is the effect of c on the graph of y=f(x) for the function y=f(x)+c ?The translation of axis on any curve y = f(x) is the shifting of the graph by a definite unit from the original equation or curve.
If the curve is given as y = f(x) ± a, then for +a , it shifts the curve on the graph upwards on y axis by a units and for -a, it shifts the curve on the graph downwards on y axis by a units.
The given function is y = f(x) and thus for the graph y = f(x) + c, from the principle of translation of axis, it shifts the curve upwards on y-axis by c units.
Therefore, by translation of axis, the effect of c on the graph of y=f(x) for the function y=f(x)+c is it shifts up the curve by c units.
To learn more about translation of axis, refer -
https://brainly.com/question/13636820
#SPJ2
8. Which expression is equivalent
to 24 + 15?
A 2 X (12 + 7)
B 3 X (8 + 5)
C 5 x (8 + 3)
D 8 X (3 + 7)
Answer:
B
Step-by-step explanation:
Given
24 + 15 ← factor out 3 from each term
= 3(8 + 5)
As a check
24 + 15 = 39 and
3(8 + 5) = 3 × 13 = 39
Hence 24 + 15 = 3(8 + 5) → B
On a triangle, the vector from one vertex to another vertex is 〈-12,5〉. What is the length of the side?
Answer:
13
Step-by-step explanation:
The magnitude of a vector < a, b > is
[tex]\sqrt{a^2+b^2}[/tex]
Given < - 12, 5 > then the length of the side is
[tex]\sqrt{(-12)^2+5^2}[/tex]
= [tex]\sqrt{144+25}[/tex]
= [tex]\sqrt{169}[/tex] = 13
Final answer:
The length of the triangle side represented by the vector 〈-12,5〉 is calculated using the Pythagorean theorem and is found to be 13 units.
Explanation:
The student has asked about finding the length of the side of a triangle given a vector from one vertex to another. The vector given is 〈-12,5〉. The length of this side can be calculated using the Pythagorean Theorem for the magnitude of a vector, which states that the magnitude is the square root of the sum of the squares of the vector's components. The formula for the magnitude (or length) of a vector 〉 a, b 〉 is √(a² + b²).
For the vector 〈-12,5〉, the calculation would be:
a = -12b = 5Magnitude = √((-12)² + (5)²)Which simplifies to:
√(144 + 25)√169Magnitude = 13Therefore, the length of the side of the triangle is 13 units.
What is the simplest form of the expression (–12.7y – 3.1x) + 5.9y – (4.2y + x)?
Answer:
-11y - 4.1xStep-by-step explanation:
[tex](-12.7y-3.1x)+5.9y-(4.2y+x)\\\\=-12.7y-3.1x+5.9y-4.2y-x\qquad\text{combine like terms}\\\\=(-12.7y+5.9y-4.2y)+(-3.1x-x)\\\\=-11y-4.1x[/tex]
The simplest form of given expression is [tex]-11y-4.1x[/tex].
What is an expression?Expressions in math are mathematical statements that have a minimum of two terms containing numbers or variables, or both, connected by an operator in between.
Given expression
[tex](-12.7y-3.1x)+5.9y-(4.2y+x)[/tex]
= [tex]-12.7y-3.1x+5.9y-4.2y-x[/tex]
Combine like terms
= [tex](-12.7y+5.9y-4.2y)+(-3.1x-x)[/tex]
= [tex]-11y-4.1x[/tex]
The simplest form of given expression is [tex]-11y-4.1x[/tex].
Find out more information about expression here
https://brainly.com/question/14083225
#SPJ2
28
The elevation at ground level is O feet. An elevator starts 90 feet below ground level.
After traveling for 15 seconds, the elevator is 20 feet below ground level. Which
statement describes the elevator's rate of change in elevation during this 15-second
interval?
A
The elevator traveled upward at a rate of 6 feet per second.
The elevator traveled upward at a rate of 4 feet per second.
B
C
The elevator traveled downward at a rate of 6 feet per second.
D
The elevator traveled downward at a rate of 4 feet per second.
Step-by-step explanation:
If we graph elevation vs time, the rate of change is the slope of the line.
At t = 0, h = -90.
At t = 15, h = -20.
m = (-20 − (-90)) / (15 − 0)
m = 70/15
m = 4.67
The closest answer is B. The elevator traveled upward at a rate of 4 feet per second.
What is h(10) equal to? h:k→k^2-k
h(10)=[1]
[tex]h(k)=k^2-k\\\\h(10)=(10)^2-10=90[/tex]
Solve the equation by graphing. If exact roots cannot be found, state the consecutive integers between which the roots are located. x2 +6x +8 = 0
Answer:
Step-by-step explanation:
The roots are very clear on the graph. I have left them unlabeled so that you can put the two points in.
The points are (-4,0) and (-2,0)
The graph was done on desmos which you can look up. The box in the upper left corner was filled with
y = x^2 + 6x + 8
Solve for f(-1).
F(x) = -3x + 3
F(-1) =
F(x) = -3x + 3
replace x in the equation with -1:
F(-1) = -3(-1) + 3
Simplify:
f(-1) = 3+3
f(-1) = 6